Knowledge, attitude, and practice toward COVID-19 vaccination in Kazakhstan: a cross-sectional study - Alpamys Issanov; Zylkiya Akhmetzhanova; Dieter Riethmacher; Mohamad Aljofan (Taylor & Francis Group, 2021)
Background: There are several COVID-19 vaccines available and many are under different stages of development. However, vaccine hesitancy, including vaccination delays and refusals, represents a major hurdle for achieving herd immunity. The current study aims to evaluate COVID-19 vaccine hesitancy and the associated factors. Method: This is a cross-sectional survey-based study that was conducted between Aug and Nov 2020. Results: There were 417 respondents with nearly 61% females, more than 65% fall between the ages of 18 and 29 years, three-quarters holding a university degree, with more than 63% identified as single, and those who have no children represented more than 67% of the respondents. More than 36% of the respondents considered themselves COVID-19 vaccine hesitant. COVID-19 vaccine hesitancy appeared to be high among female respondents (p = .02), aged 30 years old and above (p < .001), widowed or divorced (p < .001) and those who have a child (p < .001). One of the most vaccine hesitancy influencing factors is the vaccines' country of origin. Conclusion: There appears to be a high COVID-19 vaccine hesitancy among the participants with several associated factors. The current finding provides a knowledge base for policymakers for communication improvement and confidence-building in relation to COVID-19 vaccines and vaccination.